Thematic Real Work Lecture (KKNT) Teaching Assistance at Village Wedi Subdistrict Gedangan Sidoarjo - Laila, Nafisah Nur; Khairunnisa, Safira Adara; Rahmawati, Diah Ayu (Department of Physics, Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Surabaya (UNESA), 2023)
KKN thematic with theme assistance Teach in Village Wedi This in a manner general aim For increase implementation education with pleasant. Activities are carried out actively from the second week of October 2022. The methods used are interviews, observation, and response questionnaires. Results questionnaire response student MTS Nurus Shafi'i on eye lesson crafts, Language Indonesia, science, And Mathematics in a manner consecutive score 4.1; 3.75; 3.95; 4,2 including in good category. Then the results of the TPQ Nurus Syafi'i response questionnaire teacher respondents score 4.55 with very good category, and TPQ student respondents Nurus Syafi'i obtained a score of 4.42 including the very good category. As well as for results questionnaire response SDN Wedi teacher respondent a score of 4.7 categories was obtained very Good, And respondent student elementary school Wedi obtained score 4,5 including category very Good.